Efectos jurídicos del Estado de cosas Inconstitucional en Colombia, a la luz de la Jurisprudencia de la Corte Constitucional (1997 -2017) (2018)
In this monograph a conceptual study of the Unconstitutional State of Things (ECI) is made, from the perspective of constitutionalism better known as: the Social State of Law, accepted by Colombia since 1991, the relation of the meaning of Fundamental Rights to its respect and protection of them, with special emphasis on vulnerable populations, likewise, deepens in the figure Unconstitutional State of Things; as well as the scope of the National jurisprudence in said declarations; it will be observed in general lines the previous antecedents at international level, that allows to the Constitutional Cut to have a contemporary vision of the Fundamental Rights; the causes that give origin to the declarations of the (ECI) by the Constitutional Court are clarified, in the same way the criteria used by the same to decree them from the landmark sentence T-025-04 are described; it delves into the positive and negative dimension of Fundamental Rights, in particular an analysis of the relationship between the declaration of the States of Unconstitutional Things and the Fundamental Rights of freedom, equality and due process; Finally, the legal effects provoked by the declaration of the Unconstitutional State of Things in the aforementioned rights are described in an argumentative manner, finally some conclusions are exposed